The role of informal learning of French as a foreign language in stimulating the metacognitive (self-)awareness of French philology students. Example of French-language films and series - Grabowska, Monika Ewa (Glottodidactica, 2022)
The research concerns a specific learning environment, namely the Institute of Romance Studies at the University of Wrocław, and attempts to address two questions: 1. To what extent do students of French philology currently benefit from the affordances offered to them by modern digital tools, in particular the various video-on-demand platforms, for informal learning of French via French-language films and series? 2. How does this activity stimulate their metacognitive awareness and self-awareness in the area of learning French as a foreign language? To this end, students of French philology took part in a survey which demonstrated that films and series are an important leisure activity, even if French-language titles represent only 21% of what they are watching. However, these films and series are subjected to important metacognitive reflection.